Well-Posed and Regular Nonlocal Boundary-Value Problems for Partial Differential Equations - Kengne, E. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
The present paper deals with the well-posedness and regularity of one class of one-dimensional time-dependent boundary-value problems with global boundary conditions on the entire time interval. We establish conditions for the well-posedness of boundary-value problems for partial differential equations in the class of bounded differentiable functions. A criterion for the regularity of the problem under consideration is also obtained.